Advanced Digital Auditing Theory and Practice of Auditing Complex Information Systems and Technologies - Berghout, Egon; Fijneman, Rob; Hendriks, Lennard; de Boer, Mona; Butijn, Bert-Jan (Progress in IS, 2023)
This open access book discusses the most modern approach to auditing complex digital systems and technologies. It combines proven auditing approaches, advanced programming techniques and complex application areas, and covers the latest findings on theory and practice in this rapidly developing field. Especially for those who want to learn more about novel approaches to testing complex information systems and related technologies, such as blockchain and self-learning systems, the book will be a valuable resource. It is aimed at students and practitioners who are interested in contemporary technology and managerial implications.